Linc-RAM is required for FGF2 function in regulating myogenic cell differentiation. Issue 3 (4th March 2018) - Zhao, Yixia; Cao, Fengqi; Yu, Xiaohua; Chen, Chuyan; Meng, Jiao; Zhong, Ran; Zhang, Yong; Zhu, Dahai
ABSTRACT: Myogenic differentiation of skeletal muscle stem cells, also known satellite cells, is tightly orchestrated by extrinsic and intrinsic regulators. Basic fibroblast growth factor (FGF2) is well documented to be implicated in satellite cell self-renewal and differentiation by repressing MyoD. We recently identified a MyoD-regulated and skeletal muscle-specifically expressed long non-coding RNA Linc-RAM which enhances myogenic differentiation by facilitating MyoD/Baf60c/Brg1 complex assembly. Herein, we investigated the transcriptional regulation and intracellular signaling pathway in mediating Linc-RAM gene expression during muscle cell differentiation. Firstly, we demonstrate Linc-RAM is negatively regulated by FGF2 via Ras/Raf/Mek/Erk signaling pathway in muscle cells. Overexpression of MyoD significantly attenuates repression of Linc-RAM promoter activities in C2C12 cells treated with FGF2. Knockout of MyoD abolishes FGF2-mediated repression of Linc-RAM gene transcription in satellite cells sorted from skeletal muscle of MyoD − / − ;Pax7-nGFP mice, suggesting inhibition of MyoD is required for FGF2-mediated expression of Linc-RAM . For the functional significance, we show that overexpression of Linc-RAM rescues FGF2-induced inhibition of C2C12 cell differentiation, indicating inhibition of Linc-RAM is required for FGF2-mediated suppression of myogenic differentiation. Consistently, we are able to further corroborate the requirement of Linc-RAM inhibition for FGF2-modulated repression of myogenic differentiation by using an ex vivo cultured single fiber system and satellite cells sorted from Linc-RAM − / − ;Pax7-nGFP knockout mice. Collectively, the present study not only reveals the intracellular signaling in FGF2-mediated Linc-RAM gene expression but also demonstrate the functional significance of Linc-RAM in FGF2-mediated muscle cell differentiation.